The prediction of distress tolerance based on the feeling of loneliness and self-handicapping in students. (15th July 2020) - Karami, Amir; Khodarahimi, Siamak; Ghazanfari, Firoozeh; Mirdrikvand, Fazlollah; Barigh, Masoud
Abstract: College is an environment with both learning opportunities and risk tasking opportunities abound. Living independently and away from parental monitoring can be both positive and anxiety provoking. One of the components that can be effective for physical and psychological health in stressful conditions is the personality trait "Distress Tolerance". The purpose of this study was to investigate the role of feeling, of loneliness and self-Handicapping in predicting student distress tolerance. The research method was descriptive and correlational. The statistical population consisted of all students of Sistan and Baluchestan University in 2018. A sample of 360 individuals was selected through multistage cluster sampling. Students completed loneliness, self-handicapping, and distress tolerance questionnaires. The results of the study showed that there is a significant negative correlation between loneliness and self-handicapping with distress tolerance. The results of a stepwise regression showed that in the first step self-handicapping and in the second step self-handicapping with loneliness were able to predict distress tolerance significantly.